The study of social-demographic and other determinants of hypertension in a rural population of North India, Delhi, India - Velu, Madhan K.; Meena, Gajendara S.; Kumar, Rajesh; Daga, Mirudula K.; Ingle, Gopala K. (International Journal Of Community Medicine And Public Health, 2016)
Background: Hypertension is emerging as a major public health problem in India and also increasing in rural population. Methods: The Community based Cross-sectional study was carried out during the year 2014 in rural area of Delhi, with the objectives to estimate the prevalence of Hypertension and to identify associated socio-demographic and other determinants. Results: Prevalence of Hypertension in rural population was found to be 21.2%; in men was 23.1% and in women it was 19.2% in the population age 20 years and above. Age, BMI, high salt-Intake, alcohol consumption, family history of hypertension was found to be significantly associated with hypertension. Conclusions: Based on high prevalence, it is recommended that a basic protocol for screening of hypertension should be made for rural population which can be used for prevention, early diagnosis, and for prevention of complications.